Analisis Determinan Perilaku Perawat dalam Penerapan Praktek Menyuntik yang Aman Di RSUD Kota Kendari - Fariki, La ode Ali; Rangki, La; Wati, Rahma (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2018)
Infections that occur in the hospital, one of which is a nosokomial infection. Injection is one of the most commonly used medical methods for drugs or prevention. The high numbers of people who take unsafe injections are a factor that causes nosokomial infections. The purpose of this study was to analyze the behavior of nurses in hospitals in Kendari City Hospital.This study used observational analytics with a cross sectional approach with a sample of 55 people conducted proportionally random sampling using the chi square test. The results showed that there was a relationship between nurse knowledge (X-hit = 6.979), nurse motivation (X-hit = 9,133), infrastructure (X-hit = 7,487), IPCLN supervision (X-hit = 7,117) with nurse behavior in Kendari City Hospital. This study is an independent variable (knowledge of nurses, advocates, facilities and infrastructure, and IPCLN supervision) relations with nurses in the practice of injecting. Gelatin can be given by the Hospital to provide information about safe injections to nurses and conduct continuous supervision of IPCLN.